Championing behavior and employee performance: The role of transformational leadership, work environment, and job stress - Olivia Barcelona Nasution; Niken Sekar Lestiyani; Marhadi Marhadi (Universitas Ahmad Dahlan, 2026)
Public sector organizations are required to continuously adapt to organizational changes and improve employee performance to deliver effective public services. In this context, leadership and workplace conditions have an important role in encouraging innovative behavior and improving employee performance. This study examines the effects of transformational leadership, work environment, and job stress on championing behavior and employee performance in the public sector. The research was conducted at the Regional Secretariat of Pemalang Regency, Central Java, Indonesia, using a quantitative approach. This study uses a census approach, in which all members of the population are included. Data were collected from 150 civil servants and analyzed using partial least squares structural equation modeling. The results indicate that transformational leadership positively affects championing behavior and employee performance. In addition, the work environment positively influences championing behavior and employee performance. However, job stress has a negative effect on championing behavior and an insignificant effect on employee performance. These findings suggest that effective transformational leadership and a supportive work environment play crucial roles in fostering innovative behavior and enhancing employee performance in public-sector organizations. This study contributes to the literature by integrating leadership, environmental, and psychological factors to explain championing behavior in a government context. The implications highlight the importance of public sector managers strengthening transformational leadership practices and creating conducive work environments to improve organizational outcomes.